Higher energy and safer sodium ion batteries via an electrochemically made disordered Na3V2(PO4)2F3 material - Yan, Guochun; Mariyappan, Sathiya; Rousse, Gwenaelle; Jacquet, Quentin; Deschamps, Michael; David, Renald; Mirvaux, Boris; Freeland, John William; Tarascon, Jean-Marie (Nature communications, 2019)
The growing need to store an increasing amount of renewable energy in a sustainable way has rekindled interest for sodium-ion battery technology, owing to the natural abundance of sodium. Presently, sodium-ion batteries based on Na 3 V 2 (PO 4 ) 2 F 3 /C are the subject of intense research focused on improving the energy density by harnessing the third sodium, which has so far been reported to be electrochemically inaccessible. Here, we are able to trigger the activity of the third sodium electrochemically via the formation of a disordered Na x V 2 (PO 4 ) 2 F 3 phase of tetragonal symmetry ( I 4 /mmm space group). This phase can reversibly uptake 3 sodium ions per formula unit over the 1 to 4.8 V voltage range, with the last one being re-inserted at 1.6 V vs Na + /Na 0 . We track the sodium-driven structural/charge compensation mechanism associated to the new phase and find that it remains disordered on cycling while its average vanadium oxidation state varies from 3 to 4.5. Full sodium-ion cells based on this phase as positive electrode and carbon as negative electrode show a 10–20% increase in the overall energy density. Na 3 V 2 (PO 4 ) 2 F 3 is a promising cathode material for Na-ion batteries, although its third sodium is usually not accessible electrochemically. Here the authors realize a disordered tetragonal NVPF phase, which can reversibly uptake 3 Na-ions and enables improved energy density for the NVPF/C full cell.